Urban marketplace qualities for cultural and economic regeneration - Zakariya, Khalilah; Zen, Ismawi; Harun, Nor Zalina; Kamaruddin, Zumahiran; Zainal Abidin, Norzalifa; Hj. Baharuddin, Zainul Mukrim; Abd Ghapar, Muhammad Hazrin; Mohd, Siti Zulaikha (2017)
Urban markets have been recognized in published works as a significant attraction in urban tourism. Many cities redevelop their urban markets to sustain the local culture and the informal economy, particularly when the markets are a potential tourist attraction. However, there has yet been a research that identifies the marketplace qualities in Malaysia and what they mean to locals and tourists from both cultural and economic perspectives. The aim of this research is to examine the qualities of the urban public markets that contribute to their cultural and economic vitality. The objectives are: 1) To identify the tangible and intangible qualities of the urban markets through examining the setting, spaces, products and activities; 2) To analyse the perceptions of the vendors and the visitors towards the markets; and 3) To synthesize the values of the markets from the aspects of social, culture and economy.This research adopted a case study approach, through examining two public markets in the urban context, which are Pasar Kedai Payang in Terengganu and Pasar Siti Khadijah in Kelantan. The methods comprised of three stages: 1) Gathering data from the inventory and mapping of the market spaces; 2) Conducting semi-structured interviews with 80 market vendors; and 3) Conducting survey questionnaire on 994 market visitors. The findings of the research reveal three main discoveries. First, the markets’ qualities as tourist attractions are primarily attributed to their local products and the presence of local vendors. However, in terms of tourism infrastructure, both markets still need to be further improved. Second, in relation to this, the local products and the local vendors contribute significantly to the markets’ cultural sustainability. The markets need to be developed with strategies that can foster the continuity of the local products and business viability for the local vendors. Third, the markets contribute greatly to the local economy, particularly for the informal vendors. The new model of urban marketplace qualities from this research can guide the governing authority, built environment practitioners, the vendor associations and other researchers develop public markets while sustaining their cultural and economic richness.